Surgeon has no abacus, but only anatomical benchmarks - Rausei, Stefano (Translational Gastroenterology and Hepatology, 2019)
In gastric cancer management the extension of the gastric resection, and hence the type of lymphadenectomy, is related to the tumor site and tumor stage, as well as to patients age and comorbidities, possibly influencing surgeons’ decision.